Kolase dalam Pembelajaran Sekolah Dasar: Sintesis Tematik dan Model Konseptual Pengembangan Motorik Halus - Durroh Nasihatul Ummah; Maulana Paramaditya Ananta; Ahmad Bagus Al Hilal; Fananda Aprilia Nurbaity (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2026)
Fine motor development is an essential aspect of elementary education, as it supports students in performing various academic tasks, including writing, drawing, and object manipulation. Although numerous studies have reported the effectiveness of collage activities in improving fine motor skills, existing findings remain fragmented and have yet to provide a comprehensive conceptual understanding. This study aimed to synthesize empirical findings on the implementation of collage activities in elementary school learning and to develop a conceptual model based on the synthesized evidence. A qualitative approach was employed using a literature review, while data were analyzed through thematic synthesis. The literature selection followed the PRISMA 2020 guidelines, resulting in seven empirical studies that met the inclusion criteria. The synthesis identified four major themes: (1) collage activities improve hand–eye coordination; (2) collage activities enhance the strength and control of small hand muscles; (3) collage activities improve precision and manipulative skills; and (4) collage activities promote active learning experiences that support fine motor development. Based on these themes, a conceptual model was developed to explain the relationship between manipulative collage activities, sensorimotor stimulation, fine motor skill development, and their implications for elementary school learning. The findings reinforce collage as not only an art-based learning activity but also a pedagogical strategy that systematically supports fine motor development while providing a conceptual framework for instructional design in elementary education.